2007
DOI: 10.1016/j.livsci.2007.01.152
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effect of in-feed administration of a clinoptilolite-rich tuff on certain biochemical and hematological parameters of growing and fattening pigs

Abstract: The effect of the long-term dietary use of a clinoptilolite-rich tuff (Cp) on certain biochemical and hematological parameters was studied in pigs. Forty-eight healthy piglets (24 females and 24 males) were used in the study, equally allocated in two experimental groups, depending on the inclusion or not of Cp in their feed (Cp+ and Cp− groups respectively). Cp was incorporated in their feed at the inclusion rate of 2% and was administered continuously from weaning to slaughter. All pigs were individually weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 28 publications
3
28
3
8
Order By: Relevance
“…There was no significant clear trend in selected electrolytes in response to increasing dietary zeolite, being consistent with the reports from terrestrial animals (Alexopoulos et al, 2007;Demirel et al, 2011). However, Khodanazary et al (2013) reported that dietary zeolite addition increased blood Ca and K levels, decreased Na concentrations and did not change Mg levels in common carp.…”
Section: Resultssupporting
confidence: 90%
“…There was no significant clear trend in selected electrolytes in response to increasing dietary zeolite, being consistent with the reports from terrestrial animals (Alexopoulos et al, 2007;Demirel et al, 2011). However, Khodanazary et al (2013) reported that dietary zeolite addition increased blood Ca and K levels, decreased Na concentrations and did not change Mg levels in common carp.…”
Section: Resultssupporting
confidence: 90%
“…These studies documented that even long-term feeding did not affect levels of total serum protein, albumin and mineral elements in pigs Alexopoulos et al, 2007). Some studies have reported changes in glucose, cholesterol and AST levels (ConcepcionRosabal et al, 1997;Alexopoulos et al, 2007;Prvulovic et al, 2007). The present study did not find any changes in Fe distribution and haematological parameters in piglets.…”
Section: Discussionsupporting
confidence: 50%
“…The structure and physical-chemical characteristics of these clay minerals and kaolin, which is a phyllosilicate mineral, are similar . A significant increase in the body weight gain and improved conversion of feed containing clay minerals has been shown by numerous studies (Pond et al, 1981(Pond et al, , 1988Vrzgula et al, 1982;Bartko et al, 1983;Pond and Yen, 1987;Castro and Iglesias, 1989;Cabezas et al, 1991;Papaioannou et al, 2004;Chen et al, 2005;Kolacz et al, 2005;Papaioannou et al, 2005;Alexopoulos et al, 2007;Prvulovic et al, 2007). Naturally, their effect on the efficiency of animals is associated with the type, physicochemical and structural qualities, purity and proportion of these minerals in the diet (Pond and Yen, 1987;Pond et al, 1988;Papaioannou et al, 2004Papaioannou et al, , 2005, and by the age of animals (Papaioannou et al, 2004;Alexopoulos et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations